Health-related outcomes of new grocery store interventions: a systematic review. Issue 12 (1st June 2017) - Abeykoon, AM Hasanthi; Engler-Stringer, Rachel; Muhajarine, Nazeem
Abstract: Objective: To assess the evidence of the impact of new food store (supermarket/grocery store) interventions on selected health-related outcomes. Design: A systematic review following the Effective Public Health Practice Project guidelines. All quantitative studies were assessed for their methodological quality. Results were synthesized narratively. Setting: Eight electronic databases – MEDLINE, EMBASE, CINAHL, ProQuest Public Health, Web of Science, Scopus, PsycINFO and Cochrane Library – were searched to identify relevant records. Subjects: Peer-reviewed scholarly journal articles on new grocery store/supermarket interventions with adult study populations, published in the English language after 1995. Results: Eleven records representing seven new grocery store interventions were identified. Six were assessed having 'weak' methodological quality, one as 'moderate' and two as 'strong'. All studies reported fruit and vegetable consumption but results were not consistent, some studies reporting significantly more and others no increase in consumption. BMI and self-rated health did not show significant improvements. Perceptions of food access, neighbourhood satisfaction and psychological health showed significant improvements. Conclusions: Improved food access through establishment of a full-service food retailer, by itself, does not show strong evidence towards enhancing health-related outcomes over short durations. Presently the field is developing and the complex linking pathways/mechanisms are yet to be elucidated. Further evidence, in the form of high-quality research in different communities with longer follow-up periods, is needed to inform policy decisions.